2016
DOI: 10.1186/s12894-016-0166-2
|View full text |Cite
|
Sign up to set email alerts
|

10-Year experience regarding the reliability and morbidity of radio guided lymph node biopsy in penile cancer patients and the associated radiation exposure of medical staff in this procedure

Abstract: BackgroundThe guidelines of the European Association of Urologists (EAU), of the German Society of Nuclear Medicine (DGN), and the European Society for Medical Oncology (ESMO) recommend sentinel lymph node biopsy (SLNB) for lymph node staging in penile cancer with non-palpable inguinal lymph nodes as one diagnostic method. Despite this, the method is neither widely nor regularly applied in Germany – the same applies to many other countries, which may be due to insecurity in dealing with open radioactive tracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…and Lützen et al. only observed regional recurrence after secondary but not after primary DSNB, which argues against this hypothesis ( 40 , 41 ). Similarly, it is unclear whether DSNB is reliable in patients with local recurrence or previous inguinal surgeries who may have an altered lymphatic drainage, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Lützen et al. only observed regional recurrence after secondary but not after primary DSNB, which argues against this hypothesis ( 40 , 41 ). Similarly, it is unclear whether DSNB is reliable in patients with local recurrence or previous inguinal surgeries who may have an altered lymphatic drainage, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of DSNB is controversial. Two single-center studies suggested that DSNB was a reliable procedure for LN staging in cN0 patients after previous resection of the primary tumor ( 38 , 39 ), while other authors observed regional recurrence after secondary, but not after primary DSNB, arguing against this hypothesis ( 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of using a radioisotope include good tissue penetration, enabling the detection of deeper LNs, as well as preoperative visual information (with the use of a gamma camera) and acoustic guidance during operation (generated by a gamma probe). However, significant restrictions related to the use of these markers should be noted, such as the need to have a nuclear medicine department, a specific period of time in which the procedure should be performed (related to the radiotracer decay), and exposure to ionizing radiation of medical staff (which, while maintaining standard safety procedures, is at a low, safe level) [18]. A meta-analysis conducted on a large group of patients with breast cancer has proven the high accuracy of this method in detecting SLNs, with detection rates ranging between 85 and 100% [19].…”
Section: Markers and Imaging Methodsmentioning
confidence: 99%